Impact of university resources on student complaint in Malaysian Higher Education Institutions - Omoola, Sodiq Olalekan; Bakare, Kazeem Kayode; Amasa, Firdausa Al-Jannah (IATED Academy, 2022)
This paper examines the relationship between university resources and student complaint management in Malaysian Higher Education Institutions (HEIs). The discussion is premised on Organisational Justice theory (OJT) which conceptualized complaint handling, satisfaction, and fairness among stakeholders in the educational domain. The experience of students in the use of online and offline university resources varies across different levels of education. Based on the diverse complaint handling mechanisms in the Malaysian HEIs, this paper adopts a quantitative method using a survey research design. An online survey was administered to 381 students in Malaysian higher education institutions (HEIs). The findings indicated that offline resources and online resources contribute substantially to students' complaints. This study establishes the significance of an effective complaint handling mechanism for continuous feedback and improvement in HEIs.